Psychological differences and similarities between vegans, prospective vegans, and vegetarians. Motivation, knowledge, vegan literacy – and cheese - Mayrhofer, Roland; Roberts, Lara M.; Hackl, Julia M.; Frischholz, Katja (Frontiers in Psychology, 2024)
Increasing awareness of the negative environmental impact of meat and dairy consumption and production has -together with animal welfare and animal rights -led to a growing number of people following a more sustainable diet, namely a vegetarian or a vegan diet. Thus, exploring the psychological mechanisms underlying more sustainable or less sustainable diets is highly relevant for the environmental challenges of our time. Despite the fact that vegan and vegetarian diets and lifestyles differ significantly from each other, among other things, notably in their respective consequences regarding animal welfare and their ecological impact, vegans and vegetarians are often grouped together and usually compared to omnivores in psychological research. Considering that vegans and vegetarians often share similar motives for their lifestyle choices, namely animal and environmental issues, the question arises why similar motives lead to different conclusions and correspondingly different behaviours, which is of interest seeing as there are major differences regarding animals and the environment between vegans and vegetarians. This is why the following study explored the psychological differences between vegans, vegetarians, and prospective vegans -the latter group being located in an intermediate, transitionary position. Focussing on the motivational, affective and cognitive components of dietary transition and participants' adherence to eating patterns, reasons for said patterns, possible hinderances to becoming vegan, the role of participants' social environments and the impact of various misconceptions regarding the feasibility of a vegan diet in everyday life were all explored. By conducting an observational study via online questionnaire (1420 participants) significant differences were found between vegans, prospective vegans, and vegetarians, especially concerning their knowledge of issues pertaining to their respective lifestyles. Therefore, the concept of vegan literacy is proposed to explain these differences, particularly at the behavioural level. Additionally, this study explored the distinctive role of cheese, discussing possible indications of its potentially addictive nature and, consequently, the importance of cheese as a hindering factor for pursuing a vegan diet.